CP-045 Electronic prescribing: the development of a paediatric drug database. (24th March 2015) - Terry, D; Reynolds, F; Sinclair, A; Caffrey, J; Burridge, A; Bugg, N; Hussain, A; Terry, A; Terry, J; Junaid, E
Abstract : Background: A standardised electronic paediatric drug database was needed in order to aid paediatric drug dose selection within both prescribing and clinical pharmacist screening. Purpose: To determine a system of information inputs and checks to support the development of an electronic paediatric drug database (DD). The DD is designed as a clinical support tool to aid paediatric drug dose selection within both prescribing and clinical pharmacist screening. Material and methods: A multi-disciplinary team was appointed that included senior and junior medical staff, senior and junior pharmacists, pharmacy technicians, data analyst/database engineer, nursing staff and project manager. The DD was built in MS Access 2007. Information arbitration is provided by a senior oversight team consisting of the Deputy Chief Medical Officer, Chair of Drugs and Therapeutics Committee and Director of the Academic Practice Unit (a clinical pharmacist). Results: Common data sources used in clinical practice were identified as suitable for information harvesting. The DD system is based on 5 core data fields: Drug, Indication, Route, Age, and Dose; known as DIRAD. Each DIRAD is unique with processes in place to ensure they are not duplicated. Input of a draft DIRAD occurs at level 1 (L1), which is the lowest level in the 5 level process. Passage through the system to final approval at L5 requires acceptance of the DIRAD at each and every level in the process. To date (July 2014) over 3, 000 DIRADs have been entered into the system representing 765 drug entities. Reference to relevant dm + d codes is allowed within the DD structure. Migration of the system to a Sequel Server (SQL) platform is planned. Conclusion: The developed 5 stage process has been successfully used to capture and validate clinical information suitable to support electronic prescribing of medicines for paediatrics. References and/or Acknowledgements: No conflict of interest.